THE SHARIA BANK SYNDICATION FINANCING IN THE ECONOMIC LAW PERSPECTIVE - Sholihin, Riadhus (Journal of Economicate Studies, 2018)
The development is carried out by the state aimed at public welfare, especially with the presence of large-scale projects that require large funds as well. But this is constrained by capital. Islamic banking can take the opportunity by financing. However, Islamic banking is limited in providing capital to debtors and there are also rules regarding the maximum limit of financing. To answer these problems, syndicated banking cooperation with other financial institutions is needed in fulfilling financing capital needs. However, arrangements regarding syndication of Islamic banks are inadequate with the needs of Islamic banking in conducting sharia syndicated financing. This paper examines the legal aspects of Islamic economics in syndicated bank financing